Les fossiles de Cro-Magnon (Les Eyzies-de-Tayac, Dordogne) - Dominique Henry-Gambier (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The Cro-Magnon skeletal remains discovered en 1868 near les Eyzies–de-Tayac (Dordogne) are generally attributed to the Aurignacian culture, and are dated to 30000 BP through comparison with the 14C date of the Aurignacian levels of the Pataud rock shelter (Dordogne).An AMS 14C date (27680 ≠ 270 BP, Beta –157439) of a Littorina shell associated with these human remains demonstrates that they postdate 28000 BP, indicating that the Cro-Magnon burials should not be interpretated as early Aurignacian. Cultural indications and the AMS date of the shell favour an attribution to the early Gravettian period.